Patriotic education as a factor of confrontation of extremist activity - A.I. Kirsanov (Язык и текст, 2018)
Extremism and its Supreme manifestation - terrorism in the twenty-first century has become one of the most serious security problems. Extremism and terrorism in all their forms are increasingly threatening the security not only of many countries, but also of continents and their citizens, have intimidating and paralyzing effects and psychological effects on the peoples and populations of countries, as well as serious economic, political and moral damage. It kills innocent people. Purposefully organized Patriotic education in an educational organization can become a factor in the confrontation between extremist and separatist activities and is able to rally the people around the idea of protecting the Fatherland from external and internal enemies. Patriotic education can become a unifying idea in a multinational state.